Development of Vocational Culinary Materials Using the Banabooku Application for Autistic Students - Nurjanah, Nunung; Permatasari, Adisti Putri (Jurusan Pendidikan Kesejahteraan Keluarga, Fakultas Teknik, Universitas Negeri Semarang, 2024)
The objectives of this development research are: 1) Developing vocational culinary materials based on the Banabooku application for autistic students; 2) Analyzing the feasibility of vocational culinary materials based on the Banabooku application for autistic students; 3) Analyzing students' responses to Banabooku application-based vocational culinary material. This development research uses the ADDIE Model with 5 stages which include; 1) Analyzing the Independent Curriculum used in Special Schools; 2) Designing a material development concept map by the Independent Curriculum; 3) Developing material according to the concept map; 4) Testing the material that has been developed on students to analyze student responses; 5) Provide formative evaluations to students to determine the achievement of the learning objectives that have been formulated. The results of this research are: 1) Gluten and Casein Free Industrial Food and Beverage Materials based on the Banabooku application for autistic middle and high school students in Special Schools; 2) The feasibility of the Gluten and Casein Free Industrial Food and Beverage material on the Banabooku application received assessment results from material experts of 83.4% (very feasible), language experts 81.8% (very feasible), and media experts 86.2% (very feasible). worthy); 3) Student responses to the Gluten and Casein Free Industrial Food and Beverage material based on the Banabooku application obtained a result of 82.2% (very good).